Numerical study on stability of oblique wing configuration - Syed Mohamed Ali, Jaffar; M.Shaari, Muhammad Hafiz (Faculty of Engineering, IIUM, 2023)
Oblique wing is one of the morphing wing configurations that offer a superior high speed aerodynamic performance. The mechanism in which a straight wing is being rotated by a pivot at the centre resulting swept back wing on one side and swept forward on the other side. It was proven that this configuration was able to reduce drag for a given lift at both supersonic cruise and subsonic; however, there are serious control issues. CFD analysis using SolidWorks software was performed to study and visualize the aerodynamic performance of an oblique wing for a high sweep angle. The results obtained were later used to compare with other swept configurations on its stability and control.